Determining the rational modes for low-temperature storage and for obtaining products of Japanese Quince processing with high consumer properties - Odarchenko, Dmytro; Odarchenko, Andrey; Lisnichenko, Olena; Spodar, Kateryna (Eastern-European Journal of Enterprise Technologies, 2019)
The article reports a comprehensive study into the rational modes for low- temperature storage and for obtaining the products of Japanese Quince processing with high consumer indicators by examining the kinetics of freezing and by investigating microbiological indicators of samples. The study of behavior of a representative part of Japanese Quince in the process of low temperature storage was conducted. It was found that an increase in the weight of the liquid part and a decrease in the weight of the solid part are observed at an increase in the number of cycles of freezing and centrifuging. The cryoscopic study of the product of Japanese quince processing with the use of a low-temperature calorimeter was carried out, which made it possible to regulate the temperature and the freezing rate and to record continuously the temperature of the samples. It was established that the content of the frozen moisture increases from 84.8 % to 87.0 % for the liquid part and from 63.7 % to 64.9 % for the solid part. The first and the second ranges of crystallization temperature and the temperature of melting of frozen moisture in the products of Japanese quince processing were determined quantitatively. It was noted that freezing at temperature of minus 20±2 °С contributes to complete conservation of products. The research into the changes of microbiological indicators of quality and safety of the products of Japanese Quince processing within 270 days of storage at the temperature of −18±2 °С was performed. It was found that the amount of MAFAM, yeast and mold did not exceed the requirements of DSTU 6029:2008 «Semi-finished frozen fruit and berry (crushed and puree-like) products». The obtained data indicate the consumer safety of these products during the whole storage period. The data obtained make it possible to determine reasonably the optimal modes of low-temperature storage of processed products of Japanese Quince and get certain effects from their introduction in production. This will offer an opportunity to expand the range of frozen products based on domestic raw materials.